Projections of future distribution for the Golden Parakeet (Guaruba guarouba) indicate increased extinction risk for an Amazonian flagship species - Kauê Felippe de Moraes; Marcela Guimarães Moreira Lima; Gabriela Ribeiro Gonçalves; Larissa Hasnah Queiroz dos Santos; Marcos Pérsio Dantas Santos (Global Ecology and Conservation)
Over the last few decades, tropical forests have suffered significant changes due to land use and vegetation suppression caused by activities such as monocultures, cattle ranching and mining, which have favored the process of fragmentation and deforestation. Habitat loss and fragmentation are some of the main impacts affecting biodiversity. In this context, we estimated the potential distribution of Guaruba guarouba, a Psittacine species endemic to the Amazon rainforest, to assess the effects of climate change and deforestation in a current and future scenario, as well as evaluate the representativeness of this species in the current system of protected areas in the Amazon. Our results showed a loss of 80 % and 100 % of the area suitable for the occurrence of G. guarouba in optimistic and pessimistic scenarios, respectively. We also found that this species, currently classified as Vulnerable (VU) in The International Union for Conservation of Nature's (IUCN) red list, would be classified as Critically Endangered (CR) and/or Extinct (EX) in the future. Therefore, to guarantee the conservation of G. guarouba, it is important to develop environmental protection policies, encourage the conservation of remaining vegetation and create new protected areas.